Factor of Interesting in Breastfeed Mother With Milk Formula In District of Buleleng, Bali - Ni Made Karlina Sumiari Tangkas; Putu Dian Prima Kusuma Dewi; Indrie Lutfiana; Desak Ketut Sugiartini; Luh Mariyoni; Luh Putu Sri Artadi (Universitas Andalas, 2019)
Providing formula milk is still the biggest obstacle in the success of exclusive breastfeeding. Bali Province reported as a province in Indonesia with the highest use of formula milk. This study aims to look at the percentage and factors of interest of breastfeeding mothers on formula milk. The method used is a mixed-method with questionnaire sheets and interviews. The results show the proportion of formula milk interest is 25.48%. Factors that increase interest in formula milk are higher education 3.03 times (CI 1.18-7.81: p0.02), duration of work more than 6 hours 12.22 times (CI 5.95-25.09: p 0.01), and not giving Exclusive Breastfeeding 5.85 times (CI 2.94-11.65; p 0.01). While the absence of promotion of formula reduces interest by up to 77% (OR 0.23 CI 0.13-0.42; p 0.01). The reason for the interest in formula milk is that mothers must work so that there is no time for breastfeeding, inadequate breastfeeding, and time off It is enough. Better guidance on how to store breast milk should be prioritized for working mothers not only an understanding of the benefits of breastfeeding. Health workers should review government regulation No. 33 of 2012 regarding exclusive breastfeeding to support breastfeeding and limit the use of formula milk.